Propuesta de formación para fortalecer el proyecto escuela de padres en el contexto escolar de la Institución Educativa Técnica Comercial de Santo Tomas (2020)
Objective: The present research has as its main purpose, to design a training proposal to strengthen the school project for parents of the Commercial Technical Educational Institution of Santo Tomas, taking into account the school context of the institution. Method: The study has a qualitative approach, supported by primary and secondary information sources. Results: It is expected to define the impact that training has to strengthen the school for parents project in the educational institution in the municipality of Santo Tomas. Conclusion: It is relevant to conclude about the need to rethink the training processes in the school project for parents of the institution, because this would contribute significantly to the improvement of educational quality and a greater involvement of students and parents in the educational processes of their children.